Non-governmental organizations and the sustainability of small and medium-sized enterprises in Peru an analysis of networks and discourses (Environmental policy series, 2013)
This book provides a better understanding of the changing roles of non-governmental organizations (NGOs) in promoting sustainability of small and medium-sized enterprises (SMEs) in Peru. The book focuses on the domains of organic production, business social responsibility and sustainable production. The innovative study uses a combination of network and discourse analyses to identify the main patterns and shifts in the roles of NGOs in order to deal with sustainability and the market. Two major contemporary sociological theories - ecological modernization theory and network society theory - are applied to frame the analysis. The in-depth analysis of international networks of NGOs operating in Peru provide valuable inputs in terms of changes in network and discourse patterns, and consequently, changing roles for NGOs. Remarkably, social movement, liberal market and sustainability viewpoints are